Mathematical Modelling and Numerical Simulation of the Behaviour of the Modified Icaro Dryer Sensor - Mackpayen, Auguste Oscar; Ekoe, A. A. M.; Pakouzou, Magloire (European Journal of Applied Sciences, 2024)
It has often been observed that traditionally dried coffee has a tainted taste, due to the use of fortune devices. This study was undertaken to provide an approach to solutions. The aim here is to model the modified Icaro solar dryer. This work involves the study of a single-pass solar air collector for drying coffee. The mathematical modelling of the collector is based on the nodal method applied to the electrical analogy to study the thermal exchanges. The results of the temperature profile are obtained for a velocity of 1.5 m.s-1 , an air flow rate of 0.16 kg.m-3 and an absorber surface area of 5.4 m2 . In addition, for surfaces and flow rates varying respectively from 5 m2 to 7 m2 and 0.08 kg.h-1 and 0.35 kg.h-1, we obtained peak temperatures of 72.37 °C and 80 °C respectively. This enabled us to follow the behaviour of these temperatures from top to bottom and along the length of the sensor.